Factors Affecting the Profitability of Islamic Commercial Banks in Indonesia for the Period 2021–2023: FACTORS AFFECTING THE PROFITABILITY OF ISLAMIC COMMERCIAL BANKS IN INDONESIA FOR THE PERIOD 2021–2023 - Rr Lilis Intan Permatasari; Widia Octari Diliana (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2025)
This study is driven by the importance of understanding sharia banking profitability factors. Capital Adequacy Ratio (CAR), Operational Expansion to Operating Income (BOPO), and Non-Performing Financing (NPF) effect return on assets (ROA) for Indonesian Sharia Commercial Banks from 2021 to 2023. Quantitative multiple linear regression study using secondary data from 12 OJK-listed Sharia Commercial Banks yields 36 observations. CAR positively and considerably affects ROA, highlighting the importance of capital adequacy. BOPO has a significant negative impact, proving that operational efficiency boosts profits. NPF has a positive impact on problem financing risk management. The three variables explain 69.2% of ROA variation. The study's theoretical contribution is to enrich the research on the factors influencing Sharia banks' profitability following the pandemic. Bank managers and regulators can use the findings to improve capital structure, cost efficiency, and risk management to boost financial performance.